Improving Students’ Reading Comprehension Improving the Students’ Writing Recount Text Ability by Using Think Talk Write and Self-Regulated Strategy Development - Tasvil Kristin Yavernidar Zebua; Kammer Tuahman Sipayung; Erika Sinambela (PALAPA, 2023)
Based on research conducted at SMA Negeri 2 Alasa, researchers found that there were several problems in learning to write English faced by students at SMA Negeri 2 Alasa. Students often have difficulty composing a paragraph by writing down their own ideas. Therefore, researchers conducted research entitled "Improving the students' writing recount text ability by using Think Talk Write and Self-Regulated Strategy Development at the eleventh grade of SMA Negeri 2 Alasa North Nias". This research aims to observe the improvement of students' writing skills using Think Talk Write and Self-Regulated Strategy Development, whether there was an improvement in learning outcomes and what strategies were more effectively used between the two strategies. In this research, researcher used classroom action research which is applies treatments to improve learning outcomes that are better than before. From this research, the average pre-test score for class XI-IPS was 52.14% and class XI-IPA was 42.86%. After being given Think Talk Write strategy treatment in class XI-IPS, the average post-test score was 72.35% and in class XI-IPA using Self-Regulated Strategy Development with an average score of 73.57%. From these score, it can be seen that there has been a significant improvement in students' writing abilities, namely 20.21% in class XI-IPS and class XI-IPA 30.71%. Thus, it is concluded that using Think Talk Write and Self-Regulated Strategy Development can improve students' ability in writing recount texts and in this research Self-Regulated Strategy Development is more effective than Think Talk Write strategy.